Seasonal Effect on Disease Onset and Presentation in Anti-MDA5 Positive Dermatomyositis - So, Ho; So, Jacqueline; Lam, Tommy Tsz-On; Wong, Victor Tak-Lung; Ho, Roy; Li, Wai Ling; Lau, Chak Sing; Tam, Lai-Shan (Frontiers in Medicine, 2022)
Objective To investigate the seasonal variation of disease onset and presentation in an ethno-geographically homogeneous cohort of patients with anti-MDA5 positive dermatomyositis (DM). Methods This was a multi-centered, retrospective cohort study. Adult Chinese anti-MDA5 positive DM patients were identified from the Hong Kong Myositis Registry and the Clinical Data Analysis and Reporting System from 2015 to 2020. Equal number of IIM patients without anti-MDA5 antibody were selected as controls. Line blot immunoassay was used to detect the autoantibodies. The onset of disease, presenting clinical features and subsequent complications were analyzed for any seasonality. Results A total of 110 patients with anti-MDA5 positive DM were studied. The mean age at diagnosis was 53.0 ± 12.3 years and the mean follow-up duration was 20.6 ± 23.1 months. Two third of the patients (66%) had the clinically amyopathic phenotype. Most patients (86%) had interstitial lung disease (ILD) and 42% developed rapidly progressive ILD (RP-ILD). The mortality was 40% and the commonest cause was RP-ILD. Chi-square test showed significantly less patients had symptom onset in July to September. However, no particular seasonal pattern was observed in the anti-MDA5 negative IIM controls. RP-ILD occurred more frequently in patients with disease onset in October to December. Anti-MDA5 positive DM patients with disease onset in warmer months (April to September) were more likely to have clinical muscle involvement. Conclusion Apparent seasonal patterns were noted in our ethno-geographically identical anti-MDA5 positive DM patients, but not in IIM patients in general. Certain environmental factors, particularly infection, might be implicated.